2021
DOI: 10.1094/pdis-08-20-1850-re
|View full text |Cite
|
Sign up to set email alerts
|

Population, Virulence, and Mycotoxin Profile ofFusariumspp. Associated With Basal Rot ofAlliumspp. in Vietnam

Abstract: Fusarium basal rot (FBR) is particularly problematic to Allium producers worldwide. In Vietnam, information on the profile of FBR is scarce, despite the presence of Fusarium spp. in Allium plants has long been recorded. In the present study, a total of 180 isolates of Fusarium spp. were recovered from Allium bulbs/plants showing symptoms of FBR in 34 commercial Allium fields around Da Lat, Lam Dong (Vietnam). These isolates were identified to the species level by using sequencing the ITS region and the transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…For F. proliferatum , research on its interaction with Allium is still in its infancy and no information is available on virulence factors involved in host colonization. A set of interesting cyclodepsipeptide secondary metabolites, including beauvericin (BEA) and fumonisin B 1 (FB 1 ), were recently detected in onion after artificial infection with Fusarium species (Le et al, 2020). BEA is an intracellular phytotoxin and an inhibitor of young leaf respiration (Pavlovkin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For F. proliferatum , research on its interaction with Allium is still in its infancy and no information is available on virulence factors involved in host colonization. A set of interesting cyclodepsipeptide secondary metabolites, including beauvericin (BEA) and fumonisin B 1 (FB 1 ), were recently detected in onion after artificial infection with Fusarium species (Le et al, 2020). BEA is an intracellular phytotoxin and an inhibitor of young leaf respiration (Pavlovkin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of the disease decreases with seedling age (Le et al, 2021) but becomes more severe again once the bulbs are either fully developed or at the postharvest stage (Cramer, 2000). We have previously found that the aggressiveness across Fusarium isolates associated with FBR varies according to the host developmental stage (Le et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a fear that infected onions without visual symptoms will reach markets across the country. This concern is strengthening since known toxins are produced by this pathogen genius [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an F. verticillioides strain F01.12 (accession number MZ559332 ) isolated by Tran et al (2021a) was used. In addition, five other Fusarium strains comprising F. proliferatum and F. mangiferae were isolated from maize grains in the central highlands of Vietnam ( Tran et al, 2021b ), F. oxysporum , and F. solani isolated from onion in Dalat, Vietnam ( Le et al, 2020 ) and F. graminearum PH1 isolated from wheat ( Gale et al, 2005 ) were also used. Each fungus was cultured on a PDA plate (Potato Dextrose Agar, 40 g L –1 ) (Sigma Aldrich, Overijse, Belgium) for 7 days at 25°C before performing assays.…”
Section: Methodsmentioning
confidence: 99%